Solve for y
y = \frac{\sqrt{14} + 7}{2} \approx 5.370828693
y = \frac{7 - \sqrt{14}}{2} \approx 1.629171307
Graph
Share
Copied to clipboard
2y-7=\sqrt{14} 2y-7=-\sqrt{14}
Take the square root of both sides of the equation.
2y-7-\left(-7\right)=\sqrt{14}-\left(-7\right) 2y-7-\left(-7\right)=-\sqrt{14}-\left(-7\right)
Add 7 to both sides of the equation.
2y=\sqrt{14}-\left(-7\right) 2y=-\sqrt{14}-\left(-7\right)
Subtracting -7 from itself leaves 0.
2y=\sqrt{14}+7
Subtract -7 from \sqrt{14}.
2y=7-\sqrt{14}
Subtract -7 from -\sqrt{14}.
\frac{2y}{2}=\frac{\sqrt{14}+7}{2} \frac{2y}{2}=\frac{7-\sqrt{14}}{2}
Divide both sides by 2.
y=\frac{\sqrt{14}+7}{2} y=\frac{7-\sqrt{14}}{2}
Dividing by 2 undoes the multiplication by 2.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}